Przestrzenie telewizji – przestrzenie w telewizji – przestrzenie telewizyjne. Serialowe praktyki udomawiania przestrzeni - Kisielewska, Alicja (Załącznik Kulturoznawczy, 2021)
The subject of reflection in this article are television space production practices, such as: television spaces – spaces on TV – TV spaces in the most popular Polish drama series produced since 1997 by major broadcasting television stations. I focus on the ‘communities of imagination’ as spatial communities created in TV series perceived as spatial stories. I assume that thanks to the television practices of creating real-imagined space, space is being domesticated, contradicting the idea of relocation common in postmodern culture. In this article, I propose an analysis of television spatial and image strategies that are rooted in Polish culture. The spaces created on television thanks to the work of the viewers’ imagination can be the source of the identities they construct, a way of practicing oneself with the participation of traditional television.